Contractual renegotiations and International investment arbitration : a relational contract theory interpretation of investment treaties - Florou, Aikaterini (Institut d'études politiques, 2017)
The relationship between international investment treaties and the underlying contracts remains a highly disputed matter in international investment law. This thesis explored the contract-treaty interaction by using the renegotiation of regulatory contracts in the sector of energy infrastructure as a natural experiment, with a particular emphasis on the arbitral disputes that arose from the Argentine crisis. It deployed to this end an original analytical framework drawing from transaction cost economics and relational contract theory. The result of the novel combination of these two analytical frameworks is the construction of an interpretative methodology that takes an integrated approach to the two instruments – the contract and the overarching treaty – in a way that achieves a more sustainable balance between the competing public and private interests. In particular, the thesis rests on three arguments: the first is the relational-contract nature of dynamic treaty standards, which require the long-term cooperation of the parties. The second is the status of these vague standards as default rules complemented by the provisions of the underlying contracts, which are also relational, and act as gap-fillers. The last, normative argument is that the relationship between these (default) treaty rules and the (gap-filling) contractual provisions should be determined by transaction cost economics, and specifically the goal of economizing on the transaction costs of bounded rationality and opportunism when and interpreting relational treaty standards. La relation entre les traites internationaux d’investissement et les contrats sous-jacents reste un sujet très contentieux dans le domaine du droit international de l’investissement. Cette thèse explore l’interaction entre le contrat et le traité en utilisant la renégociation des contrats règlementaires dans le secteur de l’infrastructure énergétique comme un exemple d’ « expérience naturelle », en se focalisant en particulier sur les litiges arbitraux découlant de la crise économique en Argentine. A cette fin, un cadre analytique original, s’inspirant de l’économie des coûts de transaction et la théorie du contrat relationnel. Le résultat de la combinaison originelle de ces deux cadres analytiques est la construction d’une méthodologie interprétative proposant une approche d’intégration entre les deux instruments – le contrat et le traité – d’une manière apportant plus d’équilibre entre les intérêts publics et privés souvent opposés. La thèse est fondée en particulier sur trois arguments : le premier est la nature des standards dynamiques des traités comme contrats relationnels exigeant la coopération des parties à long terme. Le deuxième est le statut de ces standards vagues comme règles par défaut, complémentés par les provisions des contrats sous-jacents, qui sont aussi relationnels et fonctionnent comme « gap fillers ». Le dernier argument, normatif, est que la relation entre ces règles (par défaut) des traites et les provisions contractuels doit être déterminée par l’économie des coûts de transaction, et en particulier le but d’économiser les coûts de transaction découlant de la rationalité limitée et l’opportunisme durant l’interprétation des standards relationnels des traités.
Keywords: Arbitrage commercial international; Contrats internationaux; Economie des coûts de transaction; Interprétation des traités; Relational contract theory; Théorie du contrat relationnel; Transaction cost economics; Treaty interpretation

Essays on Bank risk, capital and Lending - Alraheb, Tammuz (Université de Limoges, 2017)
Cette thèse examine trois questions importantes dans le secteur bancaire, à savoir le risque, les fonds propres et le crédit. Elle comprend trois essais empiriques. Le premier chapitre analyse l'impact du «printemps arabe» et de la crise financière mondiale de 2007-2008 sur la stabilité du secteur bancaire dans la région MENA. Les résultats montrent que le «printemps arabe» n'a pas eu d'effet négatif sur la stabilité des banques, alors que la crise financière mondiale a considérablement réduit leur stabilité. Le deuxième chapitre étudie le rôle joué par l'environnement institutionnel dans la mise en place de coussin de fonds propres par les régulateurs ou par les banques en interne. D’après les résultats, pour que les ratios de capital réglementaire soient efficaces, l'environnement institutionnel ne doit pas être négligé lors de la mise en place de ces ratios. Le troisième chapitre étudie les différents effets des droits des consommateurs et des créanciers sur le coût des prêts. Les résultats révèlent que le coût des prêts augmente en présence de lois strictes sur la protection des consommateurs, tandis que l'augmentation des droits des créanciers réduit ce coût.
Keywords: Bank Capital Structure; Bank foreign expansion; Bank loan growth; Banque expansion à l'étranger; Banques; Consommateur (protection); Cost of intermediation; Coût de l'intermédiation; Creditors' rights; Crise économique (2008); Croissance du crédit bancaire; Droits des créanciers; Structure du capital de la Banque

The Seller's right to cure under article 48 United Nations Convention on contracts for the international sale of goods - Mirambell i Fargas, Miquel (Universitat Pompeu Fabra, 2017)
In principle, contracts are enforceable mutually beneficial agreements. In the event of a breach of contract, many national, supranational, and international legal systems—as well as recent European harmonization projects on private law—turn to cure regimes for the furtherance of such (assumed) contractually generated welfare. Namely, a mandatory Nachfrist-mechanism, a hierarchy of remedies, and debtor’s (in sales law: seller’s) rights to cure—before and after performance date—are normative devices intended to perform and preserve contracts, employing purportedly better, more cost-effective remedies for breach. Discussion of the utility of these legal institutions undisputedly belongs to the debate on modern contract law. In this thesis, one of these cure-oriented devices is exhaustively analyzed: the seller’s right to cure after performance date under Article 48 CISG1. Whereas according to paragraph (1) the seller—provided that certain preconditions are met—can impose subsequent performance on the aggrieved buyer, under paragraphs (2-4) they can merely offer cure within a period of time, irrespective of any preconditions. Article 48 CISG’s systematic setting, comparative law framework, origin, forerunners, preconditions for existence—general and specific—performance in practice, legal consequences—with regards to both the breach-of-contract regime and the availability of other remedies under the CISG—, and economic-behavioural implications are exegetically analysed. A particular focus is given to the allocation of contractual risk (see epigraph 3.2.9). Finally, conclusions are drawn at two levels: one concerning the CISG’s regime and another related to general Contract law. En principio, los contratos son acuerdos ejecutables mutuamente beneficiosos. En caso de incumplimiento del contrato, muchos sistemas jurídicos nacionales, supranacionales e internacionales—así como los recientes proyectos europeos de armonización en derecho privado—recurren a regímenes de subsanación para promover el bienestar que presumiblemente se ha generado con el contrato. A saber, un mecanismo de un Nachfrist obligatorio, una jerarquía de remedios y derechos del deudor (en compraventa: del vendedor) de subsanar—antes y después de la fecha de cumplimiento—son instrumentos normativos destinados a dar cumplimiento a los contratos y a preservarlos por medio de remedios, a priori, económicamente más eficientes. La discusión sobre la bondad y utilidad de estas instituciones indudablemente pertenece al planteamiento de un derecho de contratos moderno. En esta tesis se analiza exhaustivamente uno de estos instrumentos de subsanación: el derecho del vendedor a subsanar después de la fecha de entrega en virtud del artículo 48 CISG2. Mientras que de acuerdo con su párrafo (1) el vendedor –reuniendo ciertas condiciones previas– puede imponer una ulterior ejecución al comprador perjudicado; en virtud de los párrafos (2-4), éste solamente puede ofrecer una subsanación dentro de un plazo, pero independientemente de cualquier condición previa. Del citado artículo 48 se analizan exegéticamente el entorno sistemático, el marco en derecho comparado, el origen, los precursores, las condiciones previas para la existencia—generales y específicas—, su ejecución en la práctica, las consecuencias jurídicas—en el régimen del incumplimiento del contrato y en la disponibilidad de otros remedios bajo la Convención—así como las implicaciones económicas y conductuales. Se hace una contribución en relación con la asignación del riesgo contractual (véase infra 3.2.9). Finalmente, se extraen conclusiones a dos niveles: uno enfocado al régimen de la Convención y otro relativo al Derecho de contratos en general.
Keywords: Artículo 48 CISG2; CISG; Derecho del vendedor; Seller's right

Conflict of treaty-norms in investment arbitration - Atanasova, Dafina (Université de Genève, 2017)
The study analyses the process through which investment arbitral tribunals identify and resolve conflicts between investment standards of protection and norms from other international regimes relevant for the merits of the dispute. It questions the validity behind the current approach that tribunals adopt, under which arguments based on extraneous norms are overwhelmingly unsuccessful and proposes its' transformation in three respects. First, rather than being a mere means of interpretation, as in current practice, a broader pool of international norms must be applied to the substance of investment disputes. Second, the concept of normative conflict must be broadened if one is to address the actual challenges that inter-regime conflicts pose for international law. Third, fleshing out the modalities under which one could use private international law as a source of inspiration in public international law context, the study offers best practices for approaching the types of conflict commonly found in investment disputes.
Keywords: Arbitrage; Arbitrage d'investissements; Arbitragem; Arbitration; Diversification; Droit international; Droit international privé; Fragmentation; International courts and tribunals; International law; Investissements; Investment arbitration; Investments; Private international law

Regional trade integration and co-operation in Southern Africa : the case of the Southern African Development Community (SADC) - Mathebe, Mpubane Mox (University of South Africa, 2017)
Mercantile Law
Keywords: Economic integration; Foreign economic relations; Foreign trade regulation; Free Trade; Monetary unions; SADC; Southern African Development Community

The regulation of unsolicited electronic communications (SPAM) in South Africa : a comparative study - Tladi, Sebolawe Erna Mokowadi (University of South Africa, 2017)
The practice of spamming (sending unsolicited electronic communications) has been dubbed “the scourge of the 21st century” affecting different stakeholders. This practice is also credited for not only disrupting electronic communications but also, it overloads electronic systems and creates unnecessary costs for those affected than the ones responsible for sending such communications. In trying to address this issue nations have implemented anti-spam laws to combat the scourge. South Africa not lagging behind, has put in place anti-spam provisions to deal with the scourge. The anti-spam provisions are scattered in pieces of legislation dealing with diverse issues including: consumer protection; direct marketing; credit laws; and electronic transactions and communications. In addition to these provisions, an Amendment Bill to one of these laws and two Bills covering cybercrimes and cyber-security issues have been published. In this thesis, a question is asked on whether the current fragmented anti-spam provisions are adequate in protecting consumers. Whether the overlaps between these pieces of legislation are competent to deal with the ever increasing threats on electronic communications at large. Finally, the question as to whether a multi-faceted approach, which includes a Model Law on spam would be a suitable starting point setting out requirements for the sending of unsolicited electronic communications can be sufficient in protecting consumers. And as spam is not only a national but also a global problem, South Africa needs to look at the option of entering into mutual agreements with other countries and organisations in order to combat spam at a global level.
Keywords: Anti-spam laws; Commercial electronic messages; Consumer law; Direct marketing; Electronic commerce; Electronic communications; Electronic mail (e-mail); International cooperation; Right of privacy; Spam (Electronic mail); Telemarketing; Unsolicited commercial communications; Unsolicited electronic communications

A critical appraisal of secured transactions over personal property in Nigeria: legal problems and a proposal for reform - Otabor-Olubor, Iyare (Nottingham Trent University, 2017)
The thesis contemplates the need for Nigerian policy makers to undertake a reform of secured transactions law to meet international best standards, building upon earlier, unsuccessful, efforts by lawmakers, and drawing upon international benchmarks. It critically analyses the Registration of Security Interests in Movable Property by Banks and Other Financial Institutions in Nigeria (Regulation No.1 2015) 'CBNR' published on 2 February 2015. The CBNR, with a primary aim of facilitating affordable credit, and to modernise secured transactions law through the use of personal property as collateral, has departed from its previous position which it inherited from England. This thesis has drawn comparisons between the CBNR and prior reform initiatives particularly the Draft Law 2009 prepared by the Centre for the Economic Analysis of Law (CEAL). These reforms, which were not implemented, recommended wholesale changes to harmonise all existing secured transactions law in Nigeria. The CBNR does not follow this approach, but instead, adopts a piecemeal approach to reform. Correspondingly, this forms the framework within which this study has been undertaken with reference to whether a piecemeal or wholesale reform is now required. This thesis has followed the International Finance Corporation (IFC) approach which focuses on a three-stage secured transactions reform strategy - modernisation of the existing legal framework; establishment of an electronic collateral registry; a concerted effort towards building capacity. With the assistance of international secured transactions legal frameworks such as the UNCITRAL Legislative Guide on Secured Transactions 2007, and its Registry Guide 2014, the CBNR has been benchmarked against these adaptable legal frameworks for the purpose of harmonising secured transactions law, in search of the international best practice which may be desirable for Nigeria. The thesis identifies and discusses at length several problems and inconsistencies associated with the CNBR, and the thesis makes suggestions for a wholesale reform of the Nigerian secured transactions law. This thesis builds on existing knowledge on secured transactions law reform with particular reference, and usefulness, to sub-Saharan African countries and other developing countries that wish to attempt a similar reform of this nature.
Keywords: Nigeria; Secured transactions; Security interest; Sûretés mobilières

The impact of climate change law on the principle of state sovereignty over natural resources - Van Wyk, Sanita (Stellenbosch University, 2017)
This dissertation serves to expand the means within international law by which to address the global interdisciplinary crisis that is climate change. The principle of sovereignty over natural resources is identified as a principle of international law, evolutionary in nature, fundamentally connected to the international legal climate change regime, and able to be impacted by the effects of climate change. The gravity of climate change is illustrated, as is the intricacy and composition of the international legal climate change regime. In the process, a particular shortcoming of the international legal climate change regime is identified, namely the lack of state compliance with climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. The gravity of the effects of climate change warrants the repositioning of any principle of international law that is able to address this shortcoming of the international legal climate change regime and increase the effectiveness of the regime. In this regard it is determined, more specifically, that the gravity of the effects of climate change warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources. Climate change, forming part of the general, growing, global concern for environmental conservation and sustainable development, influences the interpretation and configuration of state rights and state duties in terms of the principle by eliciting an interpretation that restricts state rights and expands state duties. Furthermore, the gravity of the effects of climate change on the well-being of people, warrants a reinterpretation and reconfiguration of the principle of sovereignty over natural resources as a people-oriented principle as opposed to the conventional state-oriented principle, and ought to be applied with due regard to the rights of people in terms of the principle. The right of people in terms of the principle of sovereignty over natural resources, is identified as the right to economic selfdetermination, which gives effect to the right of people to dispose freely of natural resources. Should this right be promoted in future applications of the principle of sovereignty over natural resources, the right may well be established as constituting a significant basis on which people are able to hold states accountable for climate commitments made in terms of the Kyoto Protocol 1997 and the Paris Agreement 2015. In this way, the principle of sovereignty over natural resources, specifically the implementation of the right of people to dispose freely of natural resources in terms of the principle, presents a negative incentive for state compliance with climate commitments and can contribute to addressing the lack of state compliance within the international legal climate change regime. In summary, this dissertation proposes that the grave effects of climate change warrant a repositioning of the principle of sovereignty over natural resources that allows it to constitute a contribution to climate change law and the global fight against climate change.
Keywords: Climatic changes; Convention on Climate Change 1997; Convention on Climate Change 2015; Environmental law; Kyoto Protocol; Natural resources; Paris Agreement 2015; Self-determination; Sovereignty; United Nations Framework

Financial Development, Integration and Access to Finance in Africa - Essien, Grace Etim (University of Leeds, 2017)
This thesis is made up of three empirical studies that fall under the general classification of international and financial economics, particularly the study focuses on the financial system of selected African countries. The first empirical study presented in Chapter 2 examines the role of financial development in improving the effect of FDI on the economic growth of some African countries. Investigations were conducted to pinpoint which financial structure could provide the best improvement by applying the bank-based vs. market-based debate. Results from the regression analysis conducted show that the effect of FDI on economic growth becomes significant only when financial development measures were factored in. Analysis of results indicate that development of the overall financial system of African countries would be more beneficial in comparison to developing either the banks or financial markets alone. Chapter 3 empirically measures the level of financial integration in Africa’s Regional Economic Communities (RECs) using beta and sigma convergence to measure the speed and degree of financial integration in four RECs. These chapter also theoretically examines how regional financial integration contributes to financial development and economic growth in Africa. Analysis of the results show that Africa’s RECs are integrating at a relatively slow and diverse rate. Therefore, policy makers in Africa would need to focus on reform strategies that would strengthen financial integration in their regions. A fully financially integrated system would contribute immensely to financial development and promote sustainable economic growth. The fourth chapter investigates the effect of access to finance on firms’ productivity. Using cross-sectional firm-level data to estimate the effect of access to finance on labor productivity, total factor productivity (TFP), and the stochastic frontier trans-log model. This study estimates an instrumental variable (GMM) model to address potential endogeneity bias between access to credit and firms’ productivity. The results obtained show that the lack of access to finance negatively affects the productivity of firms in Africa. This study suggests that the development of a balanced financial system should be of topmost priority to policy makers. This ensures that more finance is channelled towards those firms whose productivity depends heavily on the availability of finance irrespective of their characteristics. This would result in firms increasing their investments in productivity-enhancing activities, which would benefit long-term economic growth

The taxation of small business in developing countries - AKM, Atiqul Haque (Monash University, 2017)
The thesis attempts to explore an efficient policy and administrative framework to tax the small businesses in developing countries. In order to approach the policy and administrative problems concerning the taxation of small business in developing countries this thesis asks How can small businesses be efficiently taxed in developing countries? This thesis over eight chapters qualitatively explores this research question. The analyses conclude that first, in a typical developing country a well-designed simple to follow presumptive tax regime is more efficient than the actual account based tax system. Second, this thesis argues that the noncompliance of small businesses in developing countries may not be adequately explained by the standard expected utility based compliance models. The leading tax compliance models which mainly emphasise on the perceived reward from evasion might ignore some crucial factor that constitutes the tax compliance environment of small businesses in developing countries. This thesis illustrates broadly the typical tax compliance environment of small businesses. It argues that a simple to follow tax system that requires a minimal level of taxpayer compliance would attract a section of small taxpayers into the formal tax net. Third, this thesis demonstrates that there are crucial differences between typical urban and rural businesses. A small business tax regime should have a separate set of presumptive instruments for each class of small business in order to make an efficient estimate of their economic activities. Fourth, this thesis analytically examines the presumptive methods and their practical applications. The findings suggest that in developing countries presumptive tax methods have been adopted mostly in arbitrary manner, without the objective considerations to many crucial design issues. Fifth, this thesis has developed a focused analysis on the taxation of urban small businesses in the contexts of developing countries. This thesis analyses some crucial characteristics of urban small businesses and stresses that enterprise formalization should be a key element of urban small business tax policy. For a meaningful expansion of the tax net, tax administration should put more focus on urban small businesses as these businesses have relatively more potential to grow as more stable and sustained taxpayers. This thesis concludes that a turnover based presumptive taxation is more efficient to tax the urban small businesses. Lastly, this thesis explores the issues concerning the taxation of rural small businesses. This thesis reports that the overall tax burden on the agricultural income had substantially declined over the last few decades. Developing countries should not ignore the tax potential of the rural taxpayers. In a typical developing country an asset based presumptive tax system is more efficient to tax the agricultural income of the rural small businesses. This thesis has argued that it would be more efficient to adopt a single asset based presumptive income tax replacing all the prevailing taxes on the agricultural income such as agricultural land tax, wealth tax and income tax.
Keywords: Fiscal policy; Small business taxation; Taxation administration; Taxation in developing countries; Taxation law; Taxation of rural small business; Taxation of shadow economy; Taxation of urban small business; Taxation policy

Towards responsible lending in Namibian consumer credit law : a comparative investigation - Asheela, Ndatega Victoria (University of Pretoria, 2017)
The regulation of consumer credit in Namibia mainly is provided for by the Usury Act 73 of 1968 and the Credit Agreements Act 75 of 1980. These legislative enactments originated in South Africa and were applied in South West Africa during the period of South Africa’s mandate over what is now the Republic of Namibia. Despite the fact that these enactments are over 35 years old, they are substantially unchanged. In response to an awareness of the threat of consumer over-indebtedness and other events such as financial crises, the purpose in this thesis is to undertake a situational analysis of the debt prevention measures as provided for by the Namibian legislative framework and the extent of protection these measures afford consumers in terms of irresponsible credit and over-indebtedness. A broad survey of the policies aimed at promoting responsible lending benchmarks the Namibian consumer credit regulatory framework against the leading international best principles which have been developed in response to global economic challenges. The Namibia Financial Institutions Supervisory Authority in the 2014 Microlending Bill proposes to introduce responsible lending practices in the form of a compulsory pre-agreement assessment of the prospective consumer before providing them with credit. In a comparative investigation, the creditworthiness assessment and related measures central to the responsible lending regimes in South Africa and Australia are considered. Measuring the Namibian consumer credit regulatory framework against these recent developments, it is submitted that the current debt prevention measures are inadequate in protecting consumers from irresponsible credit lending and the risk of consumer over-indebtedness. This thesis supplies reasons for the need in Namibia to update the regulatory structure of the credit industry in order to protect consumers. As a contribution to the promotion of a culture of responsible lending in the Namibian consumer credit market, the thesis proposes the introduction of responsible lending measures in Namibia’s consumer credit legislative framework.
Keywords: Consumer credit; Debt; Namibia

The impact of threshold agreements on the organisational rights of minority trade unions - Esitang, Temogo Geoffrey (University of Pretoria, 2017)
The rights of freedom of association, to organise and to bargain collectively are recognised internationally and form part of the constitutional framework of progressive and democratic states. The full enjoyment of these rights by trade unions often is hindered by the imbalance in the power relations between the employer and the representatives of the workers, hence the need for statutory intervention. The Labour Relations Act 66 of 1995 (LRA of 1995) postulates a collective bargaining regime which is voluntarist in nature and strengthens its effectiveness through a set of organisational rights and the right to strike. Incidentally, the current statutory framework for the enjoyment of organisational rights has had a direct impact on the enjoyment of the right to freedom of association and the right to organise. It is accepted that possession of the right to collective bargaining is internationally recognised as the basis of the authority to set thresholds of representivity in the workplace. The organisational rights framework in this context has been directly impacted upon. It is this direct impact that necessitates an enquiry to determine whether South Africa’s framework on the acquisition of organisational rights conforms to international standards set by the ILO and the Constitution, 1996. This thesis argues that the policy choice of the South African labour relations system in respect of some of the consequences of majoritarianism insofar as representation in individual cases is concerned does not necessarily foster the ideals of the Constitution, 1996 and the principles of international labour standards. The model of democracy as envisaged in the Constitution, 1996 is not one that promotes exclusivity. However, the effect of section 18 of the LRA of 1995, which allows threshold agreements, arguably may foster such exclusivity in the workplace. This situation has resulted in industrial democracy being a terrain of endless conflict between employers and labour, even more among trade unions themselves. As a result, the rivalry between unions in workplaces is exacerbated. The original intent behind the organisational rights of trade unions and their right to strike was to bolster their capacity to bargain collectively. It was meant to get them to focus on collective bargaining gains they can secure and to bargain more effectively. However, the current framework that favours majority trade unions has the effect of minority trade unions generally finding their existence threatened and their being systematically excluded from the acquisition of organisational rights. This study questions the power of majority trade unions to enter a collective agreement with an employer in the workplace and set unjustifiable thresholds of representivity in respect of organisational rights. This arrangement creates a hurdle in respect of the provisions of the LRA that seek to promote industrial democracy, the enjoyment of the rights to freedom of association, to organise and to engage in collective bargaining. Recent amendments to the LRA of 1995 are an attempt to mitigate the effect of sections 18 and 20 on the enjoyment of organisational rights. The CCMA, inter alia, has been granted powers to grant organisational rights to trade unions that do not meet the set threshold in terms of the empowering provisions of the LRA of 1995 if they meet certain requirements. However, these amendments do not go far enough to prevent employers and majority trade unions from continuing to set unjustifiable thresholds that can have potential to replace the determinations of the CCMA. Therefore, the study discusses the question whether the provision in the LRA of 1995 on the setting of thresholds of representivity for the acquisition of organisational rights and the concomitant amendments are in line with the democratic model envisaged by the Constitution, 1996 and to international labour standards which recognise the rights to freedom of association of minority trade unions. This research concludes by advancing recommendations pertaining to threshold agreements and the rights of minority trade unions and to what extent it is justifiable to permit them to enjoy them.
Keywords: Collective bargaining; Employer; Employeur; Labour Relations Act; Representatives workers

An appraisal of selected tax-enforcement powers of the South African revenue service in the South African constitutional context - Fritz, Carika (University of Pretoria, 2017)
There is tension between the South African Revenue Service’s duty to collect taxes on the one hand, and its duty to respect taxpayers’ rights on the other. An environment where there is clearly respect for the rights of the taxpayer may indeed result in increased voluntary compliance. This thesis constitutes a comparative appraisal of whether the following enforcement powers of the South African Revenue Service (“SARS”) in the South African constitutional context, namely (i) SARS’ power to conduct searches and seizures in order to verify compliance and investigate the commission of offences; (ii) the “pay now, argue later” rule; and (iii) the appointment of a third party on behalf of a taxpayer are in accordance with the Constitution of the Republic of South Africa, 1996 (“Constitution”). It is argued that these powers do not necessarily conform to the Constitution’s values and the fundamental rights contained in the Bill of Rights in Chapter 2 of the Constitution. To address the apparent shortcomings in the current dispensation, the thesis compares these enforcement powers of SARS with similar powers afforded to the revenue authorities of Canada, Australia, New Zealand and Nigeria. Important conclusions are drawn from this comparative review and a number of recommendations for law reform are proposed which, if implemented, would align these enforcement powers with the provisions of the Constitution. The recommendations entail, inter alia, that the seizure component of a search and seizure process should be treated separately, that half of the payment obligation should be suspended until the dispute is heard by an impartial forum, and that an objective measure must be in place to ensure that a taxpayer is able to afford basic necessities when a third party appointment is made.
Keywords: Recouvrement fiscal; South Africa; Tax-enforcement power

Governing activities in outer space: responsibility, liability, regulation and the role of insurers - Harrington, Andrea (McGill University, 2017)
As we have seen from the numerous high profile launch failures and accidents that have occurred between 2014 and 2016, space activities are still ultra-hazardous in nature, despite sixty-plus years of technological development. These activities range from essential to modern life (ex., telecommunications) to futuristic and forward thinking (ex., space tourism). In order for these activities to not only continue, but also develop and grow, this inherent risk must be managed.Further complicating the risk dynamic in outer space, States are required to take liability and responsibility for the activities of their nationals in space, including private entities and individuals. The reality of this relationship is that while States wish to promote the development of their domestic space industries, they will also usually require certain levels of insurance and indemnification to protect the State against potentially costly mishaps.With regard to outer space, political will is lacking at an international level to create new binding rules for activities in space. Likewise, States are reluctant to unilaterally impose stricter (even if ultimately beneficial) regulations on their entities for fear that their domestic industries will flee abroad to greener pastures, creating a regulatory prisoner's dilemma. These factors create a scenario where the major space insurers responsible for writing policies across national boundaries may be uniquely positioned to enforce or at least promote mechanisms to increase safety and sustainability in the commercial space industry. Increasing safety and sustainability in outer space may help to keep premium costs from growing out of control for these hazardous activities, as well. Thus, this thesis addresses three fundamental questions: 1)From a legal and policy perspective, is there a regulatory void that needs to be filled, at least temporarily?2)Are insurance companies in a position to be able to fill or partially fill that void?3)If so, how, and what actions can they undertake to improve their ability to execute that governance function?In answering these questions, this manuscript-based thesis explores the existing body of space law and common practices in space activities, including notable lacunae, and applies theories of "insurance as governance." This approach permits both analysis of the existing status of the industry and recommendations to increase the viability of space activities moving forward.
Keywords: Air and Space Law; Droit des assurances; Insurance law; Insurers; Liability insurance; Liability insurer; Responsability

China's legal obligations in the field of foreign investment : how trade agreements influence the formation of investment agreements? - Hua, Yuting (European University Institute, 2017)
Since deeper 'open-door' domestic reform in 1992, China has consistently maintained its position as the largest foreign direct investment (FDI) recipient among developing countries. In recent years China is going global as well. Accompanied with a large amount of outbound FDI, the level of debt is also increasing. Thus it is necessary for China to adopt a sustainable development policy and behave based on rules. China needs to work with the world to promote a rules-based investment climate. At a multilateral level, China joined the World Trade Organization (WTO) in 2001 and promised general and specific obligations on market entry and non-discrimination principles. Bilaterally, only after 2001, China has started negotiating preferential trade agreements (PTAs). The first part of the thesis analyses China’s legal obligations in investment agreements in pre- and post-WTO entry phases. Chapter 1 introduces China’s investment policy before 2001. Chapter 2 clarifies China’s commitments on non-discrimination principles under the WTO agreements, especially China’s Protocol of Accession. Chapter 3 compares Chinese BITs and PTAs with regard to investment principles. The second part of the thesis concerns interpretation on substantive and procedural provisions. Chapter 4 tries to answer the question of whether and how do tribunals consider jurisprudential concepts developed in the case law of the trade regime when resolving investment cases. Chapter 5 examines different remedies in trade and investment agreements. It is important for China to keep compliance with its commitments in international agreements, otherwise, it would face countermeasures which are highly costly. Also, China can implement competition rules in its domestic market for improving firms’ efficiency. Meanwhile, a balancing approach which emphasizes corporate social responsibility is equally important for China’s companies going global.
Keywords: Foreign investment; Foreign trade regulation; WTO; World Trade Organization

The African Union and the Development of African International Criminal Law - Kahombo, Balingene (Freien Universität Berlin, 2017)
This study is situated in the context of the regionalisation of international criminal law. It deals with the development of African international criminal law under the aegis of the African Union (AU). It aims to examine the factors which inform this development, the concept and the content of regional law so laid down for the African continent. The primary objective has been the exploration of theoretical and practical bases for the establishment of a viable system of African regional criminal justice in order to deal with crimes against peace and security in Africa, which put in danger African regional public order. The thesis also examines the relationship between African international criminal law and the global system of international criminal justice, currently dominated by the International Criminal Court (ICC) and the United Nations Security Council. The systemic analysis of these different issues have enabled to reach three main conclusions. First, the development of African international criminal law is not simply a conjectural consequence of the crisis observed within global international criminal law. It is also and chiefly the result of the policy of self-reliance of the AU and its member states aiming to protect and defend African regional public order through the recourse to regional institutions of criminal accountability. Second, the African Union is consequently promoting a system of African regional criminal justice based on three optional models of justice, namely the delegation of jurisdiction to a member state, the creation of hybrid courts with participation of regional judges and the establishment of a regional criminal court. Together with those crimes against peace and security that are of specific concern to the African continent, these models of justice form the core of the content of African international criminal law. However, the viability of the system towards delivering efficient justice remains problematic. There are numerous challenges to overcome, including ratifying the Malabo Protocol of June 2014 instituting the “Criminal Court of the African Union”, promoting judicial cooperation of African states and finding financial resources to support the Court’s actions. Third, African international criminal law is not a replacement of global international criminal law in the continent. There is rather a coexistence of norms and institutions which commands a certain degree of coordinated relationships to avoid competing actions and so inefficiency of justice. This thesis discusses two main approaches to consistent relationships between African regional criminal law and the global system of international criminal justice, namely the hierarchical model and the cooperative approach. It proposes a third alternative approach, that is, the regionalisation of the ICC in conjunction with the principle of regional territoriality.
Keywords: African Court of Justice and Human and Peoples' Rights; African Union; International Criminal Court; International Criminal Law; Regional Territoriality; Regionalisation; Universal Jurisdiction

Sustainable biofuel regulation and production in the SADC region : a comparative analysis - Kandala, Lupwana Jean Jacques (University of Johannesburg, 2017)
Keywords: Biofuel; Biomass energy; SADC

Trade, labour and sustainable development: an integrated perspective - Khan, Zobaida (McGill University, 2017)
Some contemporary challenges for global trade regulation and labour governance arise from the barriers between questions of law and social justice, and development policy and distributional issues. This thesis attempts to address some of these regulatory or governance challenges by exploring the interactions between sustainable development (SD), trade regulation, and social or distributive justice. Borrowing from multiple disciplines, i.e. law, international relations, and development economy, and focusing on the problems of low-income countries, this thesis examines the potential and importance of a broad ideational objective in introducing transformative changes in different regulatory or governance mechanisms. This thesis does not discuss ways to link trade regulation or labour governance with SD; rather here the possibilities of operationalizing SD, within the global trade regulatory site or transnational governance mechanisms, are explored from a capability perspective. It is argued that a capability-based understanding can resituate some questions on trade-SD interaction and introduce important behavioural changes in the functioning of the World Trade Organization (WTO). Yet, ongoing operationalization of capability-based SD requires effective market complementary interventions from governance mechanisms operating at different spaces and with diverse actors. Certain emerging transnational governance mechanisms, which connect broader social or distributional issues such as labour governance with trade opening or economic cooperation, attempt to provide crucial market complementary interventions. Taking examples from the recent transnational safety initiatives for Bangladeshi garment workers and relying on a broad conceptualization of the social or distributional issues, it is argued that attention to capability enhancement produces a much more compelling form of labour governance mechanism at these hybrid sites. With a focus on capability-based SD, a model of transformative linkage is proposed for effective labour governance. The model demands that fundamental and redistributive rights of labour are interconnected and appropriate labour governance requires a stronger form of corporate responsibility. Analyzing the interaction of diverse rules, governance processes and mechanisms, with the demands of marginalized forces the global hegemony of capital is juxtaposed with available options and possible alternatives.
Keywords: Corporate Social Responsibility; Labour; Social justice; Sustainable development; Trade regulation

Three Essays in Bank Financial Reporting - Liu, Yi (McMaster University, 2017)
This thesis investigates three important issues on bank financial reporting quality: 1) the impact of banks’ retail versus wholesale funding structure on their earnings quality, 2) the implications of economic and monetary policy uncertainty for banks’ earnings opacity, and 3) the relationship between banks’ bad time history and accounting conservatism. In the first essay, we examine the implications of banks’ funding strategies for banks’ earnings quality. We find that banks’ greater reliance on retail deposits over wholesale funds is negatively and significantly associated with the magnitude of earnings management through discretionary loan loss provisions, the likelihood of meeting-or-beating earnings benchmark, and the extent of income smoothing through loan loss provisions. This finding is consistent with the arguments that retail deposits are relatively more stable and information-insensitive, represent a more conservative business model, and attract more intensive monitoring from the Federal Deposit Insurance Corporation (FDIC) than wholesale funds, thereby improving banks’ financial reporting quality. In the second essay, we investigate whether economic and monetary policy uncertainties affect banks’ earnings opacity. When economic and monetary policies are relatively uncertain, it is easier for bank managers to distort financial information, as unpredictable policy changes make assessing the existence and impact of hidden “adverse news” more difficult for investors and creditors. Policy uncertainty also increases the fluctuation in banks’ earnings and cash flows, providing additional incentives for bank managers to engage in earnings management. Our results show that uncertainty in economic and monetary policy is associated with greater magnitude of discretionary loan loss provisions, higher likelihood of just meeting-or-beating the prior year’s earnings, and lower levels of accounting conservatism, suggesting that economic and monetary policy uncertainties lead to higher banks’ earnings opacity. In the third essay, we examine the impact of banks’ bad times on the conservatism of accounting policy. Specifically, we investigate two types of bad times: banks’ own past experiences of undercapitalization and their experiences of witnessing the failures of other banks in state-wide and county-wide crises. We find that both types of banks’ bad times are positively related to timelier recognition of earnings decreases versus earnings increases in accounting income. We also find that following exposure to bad times, banks increase their allowance for loan losses. Collectively, our results suggest that bank-specific bad times and macro-level banking crises lead to greater bank accounting conservatism. These findings support the arguments that banks exposed to past crises overweight their bad time history, and become more cautious and pessimistic about their future earnings performance and loan quality.

The notion of award in international commercial arbitration-lessons from French and English law - Marchisio, Giacomo (McGill University, 2017)
For the past twenty years, international commercial arbitration scholarship has mainly focusedon the private dimension of international arbitration. Part of a greater movement toward the privatization of justice and law, this understanding of the discipline has obscured arbitrators'adjudicative role. By reflecting on different adjudicative models and by analyzing the form andcontent of arbitral decisions, new light can be shed on our understanding of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitration; Award; Commercial Arbitration; English law; French law; International Arbitration; International commercial arbitration

Virtual property : towards a general theory - Pałka, Przemysław (European University Institute, 2017)
The primary contribution of the thesis is a theory enhancing the legal understanding of the phenomenon of virtual property, encompassing presentation of data and a new conceptual framework to interpret it. The author argues that the normative debates concerning the phenomenon have underestimated the importance of understanding and conceptualizing it first, and aims at amending this gap. The ‘virtual property phenomenon’ refers to the users of internet platforms and online computer games ‘possessing’ virtual items – digital objects that exist within these services – and getting into economic and social relations concerning these items, with other users, service providers and third parties. These relations are regulated by different types of service-specific rules – contractual and the ‘code’ – created unilaterally by the service providers, who additionally retain the ability to interpret and enforce them, using ‘digital force’, i.e. by modifying and deleting virtual items, and blocking users’ accounts. The primary challenge stems not from the fact that the phenomenon is not regulated, but from the fact that lawyers lack words – terms and concepts – to even conduct a meaningful debate about it, or how to respond to it. The thesis consists of six chapters. Firstly, the author describes the phenomenon and analyzes the theoretical and regulatory legal challenges posed by its emergence. Secondly, he critically assesses the state of the art. Thirdly, a methodology to address these challenges is proposed, which can also be used in other research projects concerning law and technology. Fourthly, the author explains how the process of digitalization has fundamentally challenged the assumptions that private law held about the structure of reality, and proposes new doctrinal tools to conceptualize it. Fifthly, the author presents a legally useful concept of virtual items, and argues that granting users property rights over them might not be the optimal means of realizing the property goals. Finally, the author proposes a normative solution, a correction of private law, responding to the new type of inequality in relations, namely a user protection law.
Keywords: Computer games; Internet; Possession (Law); Property

Libraries in the digital renaissance law and policy for book digitization - Panezi, Argyri (European University Institute, 2017)
This dissertation examines the phenomenon of book digitization and the legal challenges for the creation of digital libraries. It explores whether the current copyright framework supports libraries in the digital era as they strive to remain the institutional guardians of our literary treasures. The thesis hypothesis is that the current framework is unsuccessful or inadequate in supporting libraries. To test this hypothesis and identify the legal inefficacies the dissertation examines context, i.e. the history and rationale for applying copyright rules to books and libraries, the copyright rules as applied to libraries before and after digitization was possible, various digitization projects and the practical challenges that digitization brought about, and, the relevant litigation which has started on both sides of the Atlantic covering over a decade now. Furthermore, the thesis explores normative directions of copyright rules, including their exceptions, applicable to libraries in the digital era. It ultimately proposes that among various players claiming this role, libraries, given their institutional functions and capabilities, should be attributed rights to digitization and a favorable legal framework for providing access to digital material.
Keywords: Copyright; Digital libraries; Electronic data processing; Electronic information resources; Intellectual property; Propriedade intelectual; Propriété intellectuelle

Consumer arbitration in South Africa and its effect on the consumer's right to redress and enforcement - Rantsane, Ditaba Petrus (University of Pretoria, 2017)
The thesis entitled "Consumer arbitration in South Africa and its effect on the consumer‘s right to redress and enforcement" notes with concern the outdated and inadequate nature of the Arbitration law currently applied in South Africa. The fact that the Act was enacted in 1965 and has never been amended highlights the desperate need to review the prevailing arbitration law with a view to aligning it with the current needs of the business world. The thesis addresses the concern that consumers are not adequately protected by the current arbitration law and thus substantially develops the discourse on the topic of arbitration in situations of unequal bargaining power. It raises three primary research questions in this context. The first question reads thus, if private arbitration is properly conducted should it still provide the parties with the envisaged benefits? Secondly, is private arbitration constitutional, especially as it impacts upon consumers‘ contracting with large corporations? Thirdly, is the private arbitration process as it is currently applied, constitutional as far as it denies parties an appeal on merits against an award that is clearly wrong? The thesis attempts to answer these questions and offer recommendations for the South African Law Reform Commission (SALRC) within the specific context of commercial arbitration. In addressing these research questions, the thesis incorporates a brief overview followed by a detailed discussion of the Arbitration law framework in South Africa and abroad. The discussion of arbitration abroad is done in order to identify best practices, which could be adapted to suit the South African environment. International Arbitration law receives attention and a few observations regarding how selected foreign jurisdictions treat arbitration. Finally, the thesis explores the possibility of establishing an independent institution that will be fully equipped to handle arbitration proceedings from inception to completion.
Keywords: Consumer arbitration; Consumer rights

Non-discrimination in international economic law - Risvas, Michail (University of Oxford, 2017)
This thesis examines the jurisprudence of the World Trade Organization (WTO) Panels and Appellate Body (AB) and investment tribunals on non-discrimination clauses contained in the WTO agreements and investment agreements respectively. The thesis puts forward an alternative conceptual perspective through which the interpretation of non-discrimination provisions in international economic law could be analysed. It is argued that nondiscrimination obligations (as every legal rule to a greater or lesser extent) are inherently indeterminate. This is a fortiori the case in regard to non-discrimination provisions due to their link to the concept of equality. The concept of equality is open-ended and value-laden: its content depends on the prioritisation of different values. Thus, equality in the economic sphere can accommodate different conceptions which reflect different ideological approaches in relation to regulation, economic development and the proper role of the State in the economy. International courts and tribunals enjoy broad discretion in selecting which conception of equality to adopt when interpreting non-discrimination clauses. This indeterminacy is a positive characteristic of international economic regimes. Both the WTO and the investment arbitration regime are equipped with institutional characteristics which enable the contestation of different ideological approaches and promote pluralism. In the WTO context, this role is fulfilled by the institutional structure of the organization which facilitates the dialogue between the WTO members and the WTO Dispute Settlement System. In the realm of international investment arbitration, the mechanism of party-appointed arbitrators, despite its shortcomings which can be addressed, ensures value pluralism.

Creditors' rights in business rescue proceedings in terms of South Africa's Companies Act 71 of 2008 - Rugumamu, Victor William (University of KwaZulu-Natal, 2017)
The focus of this study is the protection of creditors’ rights in South Africa’s statutory business rescue regime provided for in Chapter 6 of the Companies Act 71 of 2008. In this analysis, three issues in particular are addressed in depth. The first is the creditors` power to initiate the business rescue process. The second is the position of creditors between the commencement and the termination of the business rescue process. The third issue is to suggest (on the basis of experience drawn from reported case law and academic criticism of the current business rescue statutory provisions) an improved model that will more effectively safeguard creditors’ rights in South Africa’s business rescue regime. In exploring these issues, I give a critical review of pertinent literature. With respect to the first issue, I conclude that the legislative provisions granting creditors the right to seek a court order initiating the business rescue process are open to criticism. By contrast, a resolution of the board of directors for the commencement of business rescue is a simpler route. With regard to the second issue I conclude that the company’s creditors have considerable influence in the business rescue process. Overall, the current statutory business rescue regime is intended to give a voice to all major stakeholders in the company’s continued solvent existence. In the event of certain irresoluble disputes in the course of that process, the judiciary has the final say. A substantial number of judicial decisions have provided interpretations of the statutory provisions, and the trend has been to try to restore financial ailing companies to solvency and viability where there is a reasonable prospect for success in this regard. In my conclusion, I propose a legislative model that seeks to strike an optimum balance between the competing and sometimes conflicting interests of the various interested parties and I suggest reforms directed at enhancing the protection of creditors’ rights. This thesis takes account of South African legislation and legislative amendments as at 31 December 2016 and of decisions of the South African courts up to and including those handed down during April 2017 and reported in the saflii on-line law reports. Since a substantial part of this thesis was written from outside South Africa, the author relied heavily on the safllii data base of judgments of the South African courts, rather than on hard copy law reports which take time to reach their destination by post.
Keywords: Financial distress; Liquidation; Rationale for business existence

Integrating healthcare quality concerns into a competition law analysis : mission impossible? - Stavroulaki, Theodosia (European University Institute, 2017)
Healthcare markets have started being created in Europe. Indeed, some European countries, such as the UK and the Netherlands, have started adopting the choice and competition model for healthcare delivery. Taking as a starting point that as health systems in Europe move towards market driven healthcare delivery, the application of competition law in these systems will increase, the goal of this doctoral thesis is (a) to identify some of the competition problems that may be raised in light of the reality that especially in hospital and medical markets the pursuit of competition and the pursuit of essential dimensions of healthcare quality may inevitably clash (b) to demonstrate that competition authorities would be unable to address some of these competition problems if they did not pose and address a fundamental question first: how should we define and assess quality in healthcare? How should we take healthcare quality into account in the context of a competition analysis? In delving into these questions, this doctoral thesis explores how the notion of healthcare quality is defined from antitrust, health policy and medicine perspectives and identifies three different models under which competition authorities may actually assess how a specific anticompetitive agreement or hospital merger may impact on healthcare quality. These are: (a) the US market approach under which competition authorities may define quality in healthcare strictly as choice, variety, competition and innovation (b) the European approach under which competition authorities may extend the notion of consumer welfare in healthcare so that it encompasses not only the notions of efficiency, choice and innovation, but also the wider objectives and values European health systems in fact pursue (c) the UK model under which competition authorities may cooperate with health authorities when they assess the impact of a specific transaction on healthcare quality. The thesis identifies the main merits and shortcomings of these models and emphasizes that what is crucial for the adoption of a holistic approach to healthcare quality is not only the model under which healthcare quality is actually integrated into a competition analysis but also competition authorities’ commitment to protect all dimensions of this notion.
Keywords: European Union countries; Medical care; Medical laws and legislation; Medical policy; Unfair competition

Problems regarding exemption clauses in consumer contracts : the search for equitable jurisprudence in the South African Constitutional realm - Tembe, Herman C. (University of Pretoria, 2017)
Keywords: Consumer contracts; Exemption clause; South Africa

The responsibility of private actors in the internal market : private actors taking over? - Trommer, Jan (European University Institute, 2017)
The picture presented and often referred to in EU internal market law and legal scholarship is clear. Within the internal market private actors are the recipients of rights and public authorities are constrained in their (regulatory) powers. The notion of this new individualism is bound up with capacities, powers, and resources that empower private actors to engage in the internal market and cross-border situations; ultimately serving the objectives the internal market seeks to attain. Yet, within thinew individualism a conceptually different class of private actors has emerged that is constrained in economic freedoms, i.e. through obligations, rather than being empowered in the context of the internal market. This thesis will enquire the reasons that led to the development of this counter-culture. Why did it emerge? To what extent does this phenomenon affect the roles of private actors in the internal market? I will demonstrate that under the counter-culture private actors are responsibilized and transformed into ‘competent authorities’, i.e. alternative forms of regulatory authority, in the internal market. Private actors are placed into systems of shared responsibilities the relationships of which are coordinated by EU internal market law. In this regard, the concept of responsibility will serve as a tool to bridge the gap between the new positions EU internal market law allocates to private actors and the emerging legal consequences, i.e. allocation of obligations or tasks. The legal contexts of EU free movement law, EU discrimination law, EU food safety law and EU data protection law will serve as case studies against which the construed conceptual framework will be tested. Under the counter-culture the new individualism is no longer only about the exercise of self-interests. Rather, this form of the new individualism comes with a requirement to give account to the interests of other actors within the internal market.
Keywords: Commercial law; European Union countries; Free Trade; Trade regulation

Identification of the parties to the employment relationship: An appraisal of teleological interpretation of statutes - Van Staden, Marthinus Jacobus (University of Pretoria, 2017)
The study, entitled “Identification of the parties to the employment relationship: an appraisal of teleological interpretation of statutes”, is a legal-interdisciplinary doctrinal investigation situated within the fields of labour law and the interpretation of statutes. It concerns itself with the proper interpretation of labour legislation in general and the interpretive question as to who should be party to the employment relationship in particular, within the context of the advent of constitutionalism and the proliferation of and the increase in the importance of labour legislation. In law, meaning-generation is a function of statutory interpretation and every application of a text to particular circumstances entails interpretation. The protection extended by labour legislation is only extended to those persons who are defined as “employees”. The study describes the teleological model of statutory interpretation, which aims to give effect to the purpose of a legislative provision in light of constitutional values. The study explores the five elements of (teleological) interpretation that should be considered when interpreting concepts such as “employee”: the text, the context, the telos (or values), the history and the comparative dimension. The chief findings of the study includes: that legislation has become an indispensable source of contemporary labour law; that the courts have adopted a teleological approach to the interpretation of statutes; that the courts have, in interpreting the term “employee”, adopted a teleological approach to the interpretation of statutes; and that the interpretations advanced by the courts have not had the profound effect envisaged by the Constitution on the transformation of society.
Keywords: Employment relationship; Labour law; Parties

The international legal framework on business and human rights and its domestic operationalisation : strategic litigation on mining and a healthy environment in South-Africa - Verdonck, Lieselot (Ghent University, 2017)
The debate on business and human rights attracts the interest of many parties, and regularly makes the headlines. On 19 January 2017 De Morgen, for instance, ran the following headline: “These banks do business with companies that violate human rights and nature”. The discourse suggests that few question that business enterprises should respect human rights. The legal meaning and consequences of associating 'business' with 'human rights' remain contentious, however. By clarifying the existing legal framework this thesis seeks to rationalize the debate. Special attention is paid to enforcing the responsibility of business enterprises for human rights through domestic judicial remedies. The analysis is concretised through a case study on adverse human rights impacts of environmental degradation caused by mining in South Africa. Based on the findings of the study, the thesis reflects on how the international legal framework on business and human rights should be developed further.
Keywords: Business; CSR; CSR disclosure; Human rights; International law; RSE; South Africa